Archetypal Hermeneutics as an Approach to the Psychology of Religion - Smythe, William E (Religious Studies and Theology, 2013)
This article develops and illustrates a hermeneutic approach to the psychology of religion derived from C. G. Jung’s psychological theory of archetypes. The point of departure is the “dis-integrative dynamics” of the failed historical collaboration between Jung and Catholic theologian Victor White. The Jung-White impasse motivates a distinction between the conceptual analysis of theological constructs and a non-conceptual hermeneutics of religious symbols. The latter form of inquiry is based on a reworking of Jung’s archetypal approach in terms of the hermeneutic notion of background understanding. This approach is then illustrated through a hermeneutic amplification of the symbolic motif of the healing serpent and its application to the theological disagreement between Jung and White. It is concluded that an archetypal hermeneutic approach is uniquely valuable for an understanding of perennial aspects of the lived experience of religious meaning.